Silver niobate perovskites: structure, properties and multifunctional applications. Issue 28 (1st July 2022) - Tian, Ye; Song, Panpan; Viola, Giuseppe; Shi, Jindou; Li, Jing; Jin, Li; Hu, Qingyuan; Xu, Yonghao; Ge, Wanyin; Yan, Zhongna; Zhang, Dou; Tarakina, Nadezda V.; et al.
Abstract : AgNbO3 exhibits anti-/ferroelectricity and narrow bandgap semi-conductivity that lead to active responses under electric field, light and force. Some of these properties are also mutually coupled and could be suited for multifunctional applications. Abstract : AgNbO3 exhibits "peculiar" anti-/ferroelectricity and narrow bandgap semi-conductivity that lead to active responses to different types of external stimuli, including electric fields, light and mechanical forces. Some of these unique properties are also mutually coupled and could be suited for the development of multifunctional devices for a broad range of applications, including dielectric, piezoelectric, high-power energy storage/conversion, photocatalytic and photovoltaic devices. In this review, recent studies of AgNbO3 and AgNbO3 -based materials are summarized. The main scope is to establish the correlations between chemical composition, synthesis conditions, structure, and properties, with an improved understanding of the phase transformations taking place in the three so called "M" phases, to ultimately provide guidance on the materials development in two key sectors: high-power energy storage and photocatalysis. Finally, current challenges in multifunctional applications and future research directions are summarized.